2005
DOI: 10.1590/s0100-39842005000200004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da tomografia de alta resolução versus radiografia de tórax na doença intersticial pulmonar na esclerose sistêmica

Abstract: OBJETIVO: Avaliar a acurácia da tomografia de alta resolução (TCAR) do tórax em relação à radiografia simples (RX) do tórax no diagnóstico de doença intersticial pulmonar relacionada à esclerose sistêmica (ES). MATERIAIS E MÉTODOS: Foram realizados TCAR e RX de tórax em póstero-anterior e perfil em 34 pacientes com diagnóstico de ES, segundo critérios do Colégio Americano de Reumatologia, e feita comparação entre as prevalências dos achados radiológicos sugestivos de doença intersticial pulmonar encontradas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…The normality of chest X-rays in the vast majority of patients confirms that this test should not be considered a first choice for interstitial impairment and that HRCT is more sensitive for the diagnosis of pre-fibrotic and potentially treatable early stages of inflammatory bowel disease [23]. The predominant respiratory symptom was cough (47%), both dry (19%) and productive (14.1%).…”
Section: Normal-n (%) Changed-n (%) P-valuementioning
confidence: 85%
See 1 more Smart Citation
“…The normality of chest X-rays in the vast majority of patients confirms that this test should not be considered a first choice for interstitial impairment and that HRCT is more sensitive for the diagnosis of pre-fibrotic and potentially treatable early stages of inflammatory bowel disease [23]. The predominant respiratory symptom was cough (47%), both dry (19%) and productive (14.1%).…”
Section: Normal-n (%) Changed-n (%) P-valuementioning
confidence: 85%
“…Even though the disease evolution time was longer in patients with tomographic alteration, the honeycombing pattern was not found, considered the most advanced stage of interstitial disease [18,19]. Studies in patients with systemic sclerosis have revealed that this pre-fibrotic stage is potentially reversible when appropriate treatment of underlying disease is instituted [23]. We consider that, because VL is an acute and treatable disease, the interstitial pneumonia found is a reversible disease.…”
Section: Normal-n (%) Changed-n (%) P-valuementioning
confidence: 94%
“…Because pulmonary changes that are detectable by routine chest X-ray in only 25-53% of cases can be detected with HRCT in up to 94% of cases, HRCT is the method of choice for the investigation of interstitial lung disease in SSc (18) .…”
Section: Discussionmentioning
confidence: 99%
“…However, it presents low sensitivity for some lesions when compared to the high-resolution computed tomography (HRCT), which can show subtle abnormalities, such as septal lines, honeycombing, parenchymal bands, and ground-glass opacity, among others [2,3]. Groundglass opacity is the increased lung attenuation in which it is still possible to identify the contours of the vessels and bronchial structures within the pulmonary area affected by a pathological process that causes a reduction in the aeration of the air spaces [4].…”
Section: Introductionmentioning
confidence: 99%